2014
DOI: 10.1155/2014/537081
|View full text |Cite
|
Sign up to set email alerts
|

Microincision Vitrectomy Surgery in Vitreomacular Traction Syndrome of Retinitis Pigmentosa Patients

Abstract: Purpose. To investigate long-term retinal changes after microincision pars plana vitrectomy surgery (MIVS) and internal limiting membrane (ILM) peeling outcome in retinitis pigmentosa (RP) patients affected by vitreomacular traction syndrome (VMT) with higher vitreous surface adhesion or coexisting epiretinal membrane (ERM). Methods. Eight RP patients suffering from VMT were evaluated by means of best corrected visual acuity (BCVA), anterior and posterior binocular examination, spectral-domain optical coherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…However, because strong vitreomacular adhesion is frequently observed in RP patients, chronic macular traction may also contribute to the ERM formation in RP. 31 Further studies including histologic investigation are needed to clarify the pathogenesis of ERM secondary to RP.…”
Section: Discussionmentioning
confidence: 99%
“…However, because strong vitreomacular adhesion is frequently observed in RP patients, chronic macular traction may also contribute to the ERM formation in RP. 31 Further studies including histologic investigation are needed to clarify the pathogenesis of ERM secondary to RP.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of ERM in RP is 1.4-51.1% [10,33]. Vitreoretinal surgery is a treatment option for the epiretinal membrane, but the available results indicate that the decision on the procedure should be taken carefully in patients with RP due to variable postoperative outcomes [34,35]. After the surgical treatment, a good anatomical result was generally obtained, but this did not improve final visual acuity [35].…”
Section: Epiretinal Membranementioning
confidence: 99%
“…Vitreoretinal surgery is a treatment option for the epiretinal membrane, but the available results indicate that the decision on the procedure should be taken carefully in patients with RP due to variable postoperative outcomes [34,35]. After the surgical treatment, a good anatomical result was generally obtained, but this did not improve final visual acuity [35]. In addition, it has been observed that even after uncomplicated ERM surgery, a patient with RP may develop severe central retinal degeneration [36].…”
Section: Epiretinal Membranementioning
confidence: 99%
“…suggests that MIVS could be an effective therapy for MH in tapetoretinal dystrophies, and according to Sandeep et al 8,[17][18][19][20] PDMS could be useful compared with air-gas tamponade since RP patients have visual field restriction that can cause movement and posture problems thus facilitating a recurrence of the disease. However, further evidence may be needed to confirm our preliminary findings.…”
Section: Surgical Proceduresmentioning
confidence: 99%